2020
DOI: 10.1021/acs.inorgchem.9b02980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lewis Acids on the Structure and Reactivity of a Mononuclear Hydroxomanganese(III) Complex

Abstract: The addition of Sc(OTf) 3 and Al(OTf) 3 to the mononuclear Mn III -hydroxo complex [Mn III (OH)(dpaq)] + (1) gives rise to new intermediates with spectroscopic properties and chemical reactivity distinct from those of [Mn III (OH)(dpaq)] + . The electronic absorption spectra of [Mn III (OH)(dpaq)] + in the presence of Sc(OTf) 3 (1-Sc III ) and Al(OTf) 3 (1-Al III ) show modest perturbations in electronic transition energies, consistent with moderate changes in the Mn III geometry. A comparison of 1 H NMR data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Very recently, however, Paine, Paul, Biswas, and co-workers reported a quite contradictory observation, in which they claimed that a [(dpaq)­Mn IV (O)] + complex, synthesized by reacting 2 with terminal oxidants, such as m -chloroperbenzoic acid ( m -CPBA), PhIO, CAN, and [Ru III (bpy) 3 ] 3+ , in the presence of protic acids (e.g., HOTf and HClO 4 ) and a redox-inactive metal ion (e.g., Sc 3+ ), does not bind metal ions (or proton) . In addition, binding of the metal ions to the metal–oxo moiety in metal–oxo complexes has been questioned in several cases . As mentioned above, metal ions and protons play a significant role(s) in modulating the chemical properties of metal–oxo species in biological and abiological reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, however, Paine, Paul, Biswas, and co-workers reported a quite contradictory observation, in which they claimed that a [(dpaq)­Mn IV (O)] + complex, synthesized by reacting 2 with terminal oxidants, such as m -chloroperbenzoic acid ( m -CPBA), PhIO, CAN, and [Ru III (bpy) 3 ] 3+ , in the presence of protic acids (e.g., HOTf and HClO 4 ) and a redox-inactive metal ion (e.g., Sc 3+ ), does not bind metal ions (or proton) . In addition, binding of the metal ions to the metal–oxo moiety in metal–oxo complexes has been questioned in several cases . As mentioned above, metal ions and protons play a significant role(s) in modulating the chemical properties of metal–oxo species in biological and abiological reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Another popular approach to modulating microenvironments is to change the electrostatic properties around M–oxido species by treating them with redox-inactive Lewis acids (LAs) such as Group II metal ions and Sc 3+ ions. The premise that these auxiliary metal ions affect function has been previously substantiated in synthetic systems. For instance, work by Agapie examined the effects of LAs on the properties of manganese-oxido clusters. Complementary work by Lau showed that in the presence of a LA, the rate of alkane oxidation by metal–oxido systems increased .…”
Section: Introductionmentioning
confidence: 99%
“…Addition of Sc(OTf) 3 to 1 . Previous studies revealed that the adding of Lewis acid (i.e., Sc 3+ ion) not only stabilize the high‐valent metal–oxo species, but also affects their oxidizing capabilities 18–29 . Experimental results are seemingly simple; species 1 , which is unreactive, is still unreactive when adding Sc(OTf) 3 ( 1‐Sc ).…”
Section: Methodsmentioning
confidence: 98%
“…The chemistry of these species has therefore been of great interest to the bioinorganic chemistry community during the past decades. Especially, redox‐inactive metal ions functioning as Lewis acids have pivotal roles in regulating the oxidizing capabilities of such metal–oxo species in many enzymatic and chemical transformations 18–29 . Previous studies have revealed that binding of a redox‐inactive metal ion can not only markedly change the reactivity, but also tune the valence tautomerization of the metal–oxo species 18,30–32 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation